Unlocking criminal law - Storey, Tony (Law teacher); Wortley, Natalie; Martin, Jacqueline, 1945- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Unlocking Criminal Law will help you grasp the main concepts of the subject with ease. Containing accessible explanations in clear and precise terms that are easy to understand, it provides an excellent foundation for learning and revising Criminal Law. The information is clearly presented in a logical structure and the following features support learning helping you to advance with confidence: - Clear learning outcomes at the beginning of each chapter set out the skills and knowledge you will need to get to grips with the subject; - Key Facts boxes throughout each chapter allow you to progressively build and consolidate your understanding; - End-of-chapter summaries provide a useful check-list for each topic; - Cases and judgments are highlighted to help you find them and add them to your notes quickly; - Frequent activities and self-test questions are included so you can put your knowledge into practice; - Sample essay questions with annotated answers prepare you for assessment; - Glossary of legal terms clarifies important definitions. This edition has been fully updated to include discussion of recent changes and developments within criminal law, including the latest case law and those laws passed in the wake of the Covid-19 crisis"--
Introduction to criminal law -- Actus reus -- Mens rea -- Strict liability -- Murder -- Homicide -- Non-fatal offences against the person -- Sexual offences -- Theft -- robbery, burglary, and other offences in the theft acts -- Fraud -- Criminal damage -- Public order offences -- Capacity defences -- General defences -- Parties to a crime -- Inchoate offences.
Includes bibliographical references and index.
Keywords: Criminal law -- England